2013
DOI: 10.2355/isijinternational.53.1195
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Shear Deformation Based on In-situ Observation of Deformation in Semi-solid Al–Cu Alloys and Water-particle Mixture

Abstract: In-situ observation of deformation at the grain scale in semi-solid Al-Cu alloys has been carried out using synchrotron X-ray radiography. The deformed microstructure was characterized by the quantitative analysis of solid motion from the image sequences during shear in semi-solid Al-Cu alloys. The influence of solid particle shape on shear deformation was also examined by comparing with in-situ observation of deformation in water-polystyrene particle mixtures where the polystyrene particles are spherical with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 25 publications
0
10
0
1
Order By: Relevance
“…This distribution of the solid vectors is consistent with the previous studies at the low shear rate of 10 À3 /s. [18][19][20][21][22] The rotation angles of solid particles during a 1.2d increment of the push plate motion were examined. Figure 4 shows the rotation field of the 67 solid particles within a 20d width.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This distribution of the solid vectors is consistent with the previous studies at the low shear rate of 10 À3 /s. [18][19][20][21][22] The rotation angles of solid particles during a 1.2d increment of the push plate motion were examined. Figure 4 shows the rotation field of the 67 solid particles within a 20d width.…”
Section: Resultsmentioning
confidence: 99%
“…The localization of high shear strain rate at the shear domain with the decreased solid fraction (i.e., a dilatant shear band [1] ) is a common characteristic with the semi-solid deformation at the low shear rate of 10 À3 /s. [18][19][20][21][22] The shear band was defined as the region of coupled localized shear strain and decreased solid fraction, as shown in Figures 11(c) ((e) through (h)) The dilation of the solid particle assembly, where liquid regions between solid particles are defined as white and solid particle boundaries are traced black. The solid particle, labeled A corresponds to that in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…28,29 However, direct in situ imaging has shown that semisolid alloys often deform by shear-induced dilation. 23,24,30,31 As an example, Fig. 2c shows a local region of microstructure where the configuration of four grains and the loading direction are similar to the geometry in Fig.…”
Section: General Phenomenamentioning
confidence: 94%